Morphological and morphometric changes on the background of cell cardiomyoplasty in experimental myocardial infarction - Estrin, Sergii; Kravchenko, Tetiana; Pechenenko, Anton (ScienceRise: Medical Science, 2020)
The aim: to study the morphological and morphometric changes in the myocardium against the background of cellular cardiomyoplasty in experimental myocardial infarction. Materials and methods: the experiment was carried out on 142 Wistar-Kyoto rats weighing 200-220 g, which were kept in the vivarium of the Department of Experimental Surgery of the State Institution “Institute of Emergency and Reconstructive Surgery named after V. K. Gusak of the National Academy of Medical Sciences of Ukraine” in the period from 2012 to 2013. The Wistar-Kyoto breed was used because it is inbred, which minimizes the rejection reaction, due to its genetic homogeneity. The animals were kept in a vivarium under conditions of 12-hour daylight hours, room temperature and access to water and food at libitum at an air temperature of +20 – + 22 °C, humidity no more than 50 %, in a light mode - day-night. The use of animals in the experiment was carried out in accordance with the rules regulated by the “European Convention for the Supervision and Protection of Vertebrate Animals used for Experimental and Other Scientific Purposes” (Strasbourg, 1986), Directives of the Council of the European Union of November 24, 1986 and the order of the Ministry of Health of Ukraine No. 32 dated 02.22.88. The induction of myocardial infarction (MI) was carried out according to the technique developed by us under general anesthesia. A separate group consisted of 20 males, whom we used as donors of mesenchymal stem cells (MSC) for further research on the Y chromosome of cell homing in the body. Cultivation of MSCs was carried out in a mixture of nutrient media DMEM / F12, 1:1, (Sigma, USA). The material for morphological studies was the sections of the myocardium of laboratory animals. To assess the morphometric parameters, histochemical methods were performed according to the recipes, which are given in the instructions for histochemistry. Immunohistochemical study was performed on paraffin sections with a thickness of 5-6 μm by the indirect Koons method according to the Brosman method (1979). Results: it was found that cellular cardiomyoplasty significantly improves the structure of the postinfarction heart, manifests itself in a decrease in the scar area and connective tissue, respectively, in an increase in the number of vessels and the percentage of preserved muscle fibers. The best results were achieved with intramyocardial injection, which requires confirmation of this fact in a clinical study. Conclusions: cellular cardiomyoplasty with any method of introducing a cell graft has a positive effect both on the morphological substrate of the heart in the form of a decrease in the size of the scar during postinfarction remodeling, an increase in the number of newly formed vessels and an increase in the percentage of preserved cardiomyocytes. This occurs due to the homing of MSCs into the ischemic zone and the commonality of two mechanisms – direct differentiation into endothelial cells of the heart vessels, as well as due to the paracrine effect